Efektifitas Metode Tabarak dalam Meningkatkan Kemampuan Tahfiz Anak Usia Dini di TK Islam Terpadu Fathurrahman Palembang - Sri Yuniarti; Fatma Rizki Intan; Bukman Lian (SENTRI: Jurnal Riset Ilmiah, 2026)
The ability to memorize the Qur'an is an important aspect of Islamic education for early childhood; however, many children still experience difficulties in memorizing verses fluently, retaining memorization over time, and maintaining interest and concentration during tahfiz activities. This condition was also identified among students of TK Islam Terpadu Fathurrahman Palembang, where monotonous learning practices limited the development of children's memorization abilities. This study aimed to analyze the effectiveness of the Tabarak method in improving the tahfiz abilities of early childhood learners at TK Islam Terpadu Fathurrahman Palembang. The study employed a Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, which was conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 15 children in Group B who participated in the Qur'an memorization program. Data were collected through observation, interviews, and documentation and analyzed using both quantitative and qualitative approaches. The findings revealed that children's tahfiz abilities improved progressively in each cycle. The percentage of achievement increased from 20% in the pre-cycle stage to 40% in Cycle I and reached 87% in Cycle II. The improvement was evident in several aspects, including fluency of recitation, accuracy of makhraj and basic tajwid, the ability to memorize without looking at the mushaf, memorization retention, and children's attitudes and enthusiasm toward memorization activities. Therefore, the Tabarak method proved to be effective in enhancing early childhood Qur'an memorization skills through listening to murattal recitations, structured repetition, the use of audio-visual media, and enjoyable learning activities tailored to children's developmental characteristics.